2019
DOI: 10.3847/1538-4357/ab4a0b
|View full text |Cite
|
Sign up to set email alerts
|

Parsec-scale Dusty Winds in Active Galactic Nuclei: Evidence for Radiation Pressure Driving*

Abstract: Infrared interferometry of local AGN has revealed a warm (∼300K-400K) polar dust structure that cannot be trivially explained by the putative dust torus of the unified model. This led to the development of the disk+wind scenario which comprises of a hot (∼1000K) compact equatorial dust disk and a polar dust wind. This wind is assumed to be driven by radiation pressure and, therefore, we would expect that long term variation in radiation pressure would influence the dust distribution. In this paper we attempt t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 70 publications
4
26
0
Order By: Relevance
“…Both show compact sizes (∼1−10 pc, Burtscher et al 2013;López-Gonzaga et al 2016). Some of the resolved model components are elongated in the polar direction, with this component accounting for most of the mid-IR emission on these scales (Hönig et al 2013;Tristram et al 2014;López-Gonzaga et al 2014Leftley et al 2019). This polar dust emission appears to be related to the large scale (up to a few hundred parsec) emission detected in the mid-IR (Cameron et al 1993;Tomono et al 2001;Radomski et al 2003;Packham et al 2005a;Asmus et al 2014;Asmus 2019;García-Bernete et al 2016) and with SOFIA at 30 µm (see Fuller et al 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Both show compact sizes (∼1−10 pc, Burtscher et al 2013;López-Gonzaga et al 2016). Some of the resolved model components are elongated in the polar direction, with this component accounting for most of the mid-IR emission on these scales (Hönig et al 2013;Tristram et al 2014;López-Gonzaga et al 2014Leftley et al 2019). This polar dust emission appears to be related to the large scale (up to a few hundred parsec) emission detected in the mid-IR (Cameron et al 1993;Tomono et al 2001;Radomski et al 2003;Packham et al 2005a;Asmus et al 2014;Asmus 2019;García-Bernete et al 2016) and with SOFIA at 30 µm (see Fuller et al 2019).…”
Section: Introductionmentioning
confidence: 88%
“…For completeness, we should mention that evidence for dust in the ionized winds of AGN outside of the dust sublimation radius is also quickly growing. Mid-infrared interferometry of nearby Seyfert galaxies with VLT/MIDI has revealed that most of the 12 µm emission on scale of tens to hundreds of parsecs originates from optically thin dust in the polar region of the inner torus, likely entrained in a ionized wind (Hönig et al 2012(Hönig et al , 2013Burtscher et al 2013;Tristram et al 2014;López-Gonzaga et al 2014Asmus et al 2011Asmus et al , 2016Hönig and Kishimoto 2017;Stalevski et al 2019;Leftley et al 2019). Recently, Mehdipour and Costantini (2018) reported the presence of dust in the X-ray wind of the nearby Seyfert galaxy IC 4329A, based on reddening measurements and the strengths of X-ray edge features from O, Si, and Fe that indicate dust depletion.…”
Section: Dust Componentmentioning
confidence: 99%
“…The origin of this polar component is still unknown. A plausible explanation is that this polar gas is the result of radiation pressure on dust grains from strong UV emission in the polar region from the accretion disk causing a dusty wind (Ricci et al 2017b;Leftley et al 2019;Hönig 2019;Venanzi et al 2020), a scenario also consistent with hydrodynamical simulations (e.g., Wada 2012).…”
Section: Introductionmentioning
confidence: 52%
“…Now, recent observations from the MID-infrared Interferometric instrument (MIDI) on the Very Large Telescope (VLT) show a large portion of the MIR spectrum of AGN stemming from the polar regions on scales of tens to hundreds of parsecs (e.g., and not only from the torus as previously thought (Stalevski et al 2017(Stalevski et al , 2019 and references therein). These observations have been made both by MIR interferometric (e.g., Burtscher et al 2013;López Gonzaga et al 2016;Leftley et al 2019) and single dish observations (e.g., Asmus et al 2016). In addition to this, ALMA is also revealing polar outflows on the same spatial scales (e.g., Gallimore et al 2016) which suggests the torus may be an obscuring outflow.…”
Section: Introductionmentioning
confidence: 90%